Geological, petrographic and geochemical evaluation of two Svecofennian ultramafic serpentinized bodies in Pernaja, SE Finland - Ingves, Jonas (My University, 2019)
When mafic-ultramafic rocks get encountered with fluids in conditions of low temperature and pressure, they are subject to an alteration form known as serpentinization. It is a process which causes several changes in the physical properties of the affected lithologies, including an increase in volume, a decrease in density, a strengthening of magnetism and an increase in the water content. Serpentinites make up a considerable volume of the upper oceanic crust, and as they inherently bear influence on e.g. the geodynamics in subduction zones and the geochemical cycle in subduction-related volcanism, a significant amount of research has focused on them during the last few decades. This thesis presents the results of a new discovery of two serpentinite bodies at Tjusterby in the southern part of the Svecofennian domain in Finland. The study object is composed of two separate bodies, both limited in size, and located completely under sea water. As such, they have been investigated through magnetometry and data gathered from till and boulder samples in neighbouring land areas. Ultramafic and amphibolitic reference samples have also been investigated from Pukkila in Päijät-Häme and Mallusjärvi in Uusimaa, both within 50 km from the Tjusterby area, as a comparison with the geological conditions recognized at Tjusterby Based on comparisons of geochemical data of the serpentinites in Tjusterby to data from serpentinites in other publications, the environment in which the ultramafic protolith in Tjusterby was serpentinized has been linked to a subduction zone, as opposed to abyssal (mid-ocean ridge) or mantle wedge environments. As a result of petrographic studies in thin sections, the Tjusterby serpentinites contain serpentine, phlogopite, opaque minerals, plagioclase and in some occasions brucite, chlorite and garnet. From the presence of brucite, and absence of talc, the protolith of the Tjusterby serpentinites is likely to have been rich in Mg, implying an olivine-rich source rock. High magnetic susceptibility in all serpentinite samples also suggests magnetite to be common among the opaque minerals. The serpentinized ultramafic bodies presented in this study are the only known of their kind in the Pernaja region, but as the Svecofennian bedrock is typically fragmented into rather small units, it is likely that similar bodies can be found in other areas in southern Finland.
Keywords: serpentinite, ultramafic, boulder tracing, magnetometry, Pernaja